2009
DOI: 10.1111/j.1365-2702.2008.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meridian acupressure for stroke patients in Korea

Abstract: Aim. To examine the effects of Meridian acupressure on the functions of affected upper extremities, activity of daily living and depression for stroke patients. Background. The handicaps of stroke patients necessitate multidisciplinary rehabilitation, which is aimed at decreasing the consequences of the illness in daily functions. In traditional Chinese medicine, Meridian acupressure has been used for rehabilitation of affected upper extremities of hemiplegia stroke patients in clinical practice. Design. Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
4
21
0
4
Order By: Relevance
“…Three studies investigated acupressure for stroke [79-81]. All three were RCTs; Shin and Lee [80] used a blocked randomised design comparing acupressure to acupressure plus aromatherapy, Kang et al [81] randomised to acupressure or control groups; McFadden and Hernandez [79] used a crossover design comparing acupressure to control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated acupressure for stroke [79-81]. All three were RCTs; Shin and Lee [80] used a blocked randomised design comparing acupressure to acupressure plus aromatherapy, Kang et al [81] randomised to acupressure or control groups; McFadden and Hernandez [79] used a crossover design comparing acupressure to control.…”
Section: Resultsmentioning
confidence: 99%
“…All three were RCTs; Shin and Lee [80] used a blocked randomised design comparing acupressure to acupressure plus aromatherapy, Kang et al [81] randomised to acupressure or control groups; McFadden and Hernandez [79] used a crossover design comparing acupressure to control. Although studies used good designs and results suggested significant improvements in pain[80], motor power [80], limb function [81], daily living[81], depression [81], and heart rate [79], all findings were limited by small unpowered samples and poor reporting, so evidence is rated at Category 2.…”
Section: Resultsmentioning
confidence: 99%
“…Terapi akupresur terutama meridian acupressure terbukti merupakan intervensi yang efektif untuk memperbaiki pergerakan ektremitas atas, meningkatkan aktivitas sehari-hari, dan mengurangi depresi pada pasien strike hemiplegia stroke di Korea (Kang, Sok, & Kang, 2009). Penelitian tersebut menguji terapi akupresur 10 menit setiap hari dalam waktu dua pecan.…”
Section: Pendahuluanunclassified
“…The exact therapeutic mechanism for the acupressure is unknown. Kang et al. (2009) have shown that acupressure has positive effects on improving the movement of the affected extremities and ADL in patients after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2001). Furthermore, acupressure in managing stroke patients may become less complex as it is not associated with pain and drug dependence (Kang et al. 2009).…”
Section: Introductionmentioning
confidence: 99%